Identifying and Analyzing Individual Factors in Creating a Conducive Environment for Retaining Human Capital and Enhancing Organizational Productivity - Sepehri, Saam; Salajeghe, Sanjar; Mollaie, Hamid Reza; Sayadi, Saeed; Shokoh, Zahra (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study aims to identify and analyze individual factors among employees that contribute to creating a conducive environment for retaining human capital and enhancing organizational productivity within the National Iranian Oil Company (NIOC). Methodology: A qualitative research design was employed, utilizing semi-structured interviews with 15 participants selected through purposive sampling. The participants included NIOC elites, consultants, and external advisors. Data were collected until theoretical saturation was achieved and analyzed using NVivo software. Thematic analysis was conducted to identify key themes and subthemes. Findings: Four main themes were identified: equal job opportunities, creating a creative environment, communication and participation, and leadership and trust. Subcategories within these themes included fair recruitment, career advancement, diversity and inclusion, innovation encouragement, flexible workspaces, professional development, transparent communication, feedback mechanisms, trustworthy leadership, and empowerment. Participants emphasized the importance of transparent hiring processes, diversity policies, innovation support, effective communication, and ethical leadership in enhancing employee satisfaction and productivity. Conclusion: The study highlights the critical role of both individual and organizational factors in creating a supportive environment for employee retention and productivity. Implementing fair recruitment practices, promoting diversity and inclusion, fostering innovation, ensuring effective communication, and ethical leadership are essential strategies for organizations.